Lithium manganate composite material and preparation method thereof, positive plate, battery and power-related equipment
By constructing metal organic frameworks on the surface of lithium manganate granules and converting into metal oxides and carbon composite materials, solve the stability and cycle life of lithium manganate materials at high temperature conditions, and realize the material. The improvement of conductivity and LI ion migration dynamics.
Patent Information
- Application Number
- CN202411866424.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-01-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The electrochemical stability and cycle life of lithium manganate materials under high temperature conditions are limited, and the conductivity and Li ion transmission efficiency of traditional metal oxide coatings are insufficient, which affects the performance and safety of the battery.
By constructing a metal organic framework coating layer (MOFs) on the surface of lithium manganate particles and converting it into a composite coating layer of metal oxide and carbon through a pyrolysis process, the conductivity of the material and Li ion migration dynamics are improved.
It significantly improves the electrochemical stability and cycle life of lithium manganate materials, enhanced the electrical and li ion migration dynamics, reduced the dissolution of MN ions, and extended the service life of the battery.
Smart Images

Figure CN119330404A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium batteries, and in particular to a lithium manganate composite material and a preparation method thereof, a positive electrode sheet, a battery and electrical equipment. Background Art
[0002] As one of the key technologies for modern energy storage, lithium battery technology has been widely studied and applied around the world. With the development of electric vehicles, portable electronic devices and large-scale energy storage systems, the demand for high-performance batteries is growing. Lithium manganese oxide (LiMn2O4), as a cost-effective and environmentally friendly cathode material, plays an important role in lithium-ion batteries.
[0003] Lithium manganese oxide has been widely studied due to its stable crystal structure and good electrochemical properties. In practical applications, lithium-ion batteries with lithium manganese oxide as the positive electrode material have shown high energy density and good cycle performance. However, its electrochemical stability and cycle life during the charge and discharge process are limited, especially under high temperature conditions, the Mn ions in the lithium manganese oxide material are easily dissolved, resulting in structural degradation and performance degradation, limiting its wide commercial application.
[0004] In order to improve the electrochemical stability of lithium manganese oxide materials in traditional technology, metal oxides are often used for surface coating. Although this strategy improves the stability of the material to a certain extent, it also brings new problems. The coating layer has poor conductivity and lacks effective Li ion transmission channels, which increases the interfacial impedance and constitutes an obstacle to the transmission dynamics of Li ions. These problems not only affect the charge and discharge efficiency of the battery, but also reduce the overall performance of the battery.
[0005] In summary, the defects in traditional technology are mainly reflected in two aspects: first, the performance of lithium manganese oxide materials is unstable under high temperature conditions, resulting in shortened battery life and safety issues; second, although the traditional metal oxide coating strategy improves electrochemical stability, its insufficient conductivity and Li ion transmission efficiency limit the further improvement of battery performance. The existence of these problems not only affects the long-term stability and reliability of the battery, but also restricts its application potential under a wider range of environmental conditions. Therefore, solving these problems is of great significance to promoting the development of lithium battery technology.
[0006] In view of this, the present invention is proposed. Summary of the invention
[0007] The first purpose of the present invention is to provide a preparation method of a lithium manganese oxide composite material, a lithium manganese oxide composite material, a positive electrode sheet, a battery and electrical equipment. The preparation method is simple, low-cost, and has the advantages of broad industrial application prospects.
[0008] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted: In a first aspect, the present invention provides a method for preparing a lithium manganese oxide composite material, by forming a metal organic framework coating layer on the surface of lithium manganese oxide particles by reacting an organic ligand with a metal salt metal, and converting the metal organic framework coating layer into a lithium manganese oxide composite material composed of a composite material of metal oxide and carbon coating the lithium manganese oxide particles through a pyrolysis process.
[0009] In an optional embodiment, the preparation method comprises: dissolving the organic ligand in a dissolving solvent to obtain a first mixed solution; Adding the metal salt and lithium manganate into water, and mixing to obtain a second mixed solution; Based on the mixing of the first mixed solution and the second mixed solution, a coordination reaction is carried out to form the metal organic framework coating layer on the surface of the lithium manganate particles to obtain a composite intermediate material; The composite intermediate material is subjected to high-temperature sintering treatment to obtain the lithium manganate composite material.
[0010] In an optional embodiment, the organic ligand is selected from at least one of a carboxylic acid ligand, a phenolic ligand and an amine ligand; and / or, The organic ligands include hydroquinone, resorcinol, 2,3,6,7,10,11-hexahydroxytriphenyl, terephthalic acid, 2-aminoterephthalic acid, 2,5-diaminoterephthalic acid, 1,3,5-tris(4-carboxyphenyl)benzene, 1,4-naphthalene dicarboxylic acid, 2,5-dihydroxyterephthalic acid, 2,2"-biphenyl dicarboxylic acid, 2,6-naphthalene dicarboxylic acid, 4,4"-stilbene dicarboxylic acid, 2,2"-bipyridine-5,5"-dicarboxylic acid, 2,2"-bipyrimidine, 2,4"-bipyridine, 2,5-dibromoterephthalic acid at least one of 2,5-diaminobenzenesulfonic acid, 2,5-thiophenedicarboxylic acid, 2,6-pyridinedicarboxylic acid, 2-methylimidazole, 2-nitroimidazole, pyrazine, imidazole, 2,4,6-tri(4-pyridine)1,3,5-triazine, tri(4-iodophenyl)amine, meso-tetra(4-carboxyphenyl)porphine, 5,10,15,20-tetra(4-pyridyl)porphyrin, meta-tetraphenylporphine, 1,3,5-tri(4-pyridyl-3-phenyl)benzene, 2,5-diaminobenzenesulfonic acid, tri(4-chlorophenyl)phosphine and 1,3,5-tri(4-pyrazolyl)benzene; and / or, The metal salt is selected from at least one of an alkaline earth metal salt, a transition metal salt or a rare earth metal salt; and / or, The chemical forms of the metal salts include nitrates, chlorides, carbonates and acetates; and / or, The metal element in the metal salt includes at least one of Al, Mg, Ca, Sr, Ba, Fe, Ti, V, Cr, Co, Ni, Zn, Cu, Ir, W, Mo, Cd, Ag, Ce, La, Pr, Nd, Sm, Eu, Os, Nb, Zr and Y; and / or, In the reaction system of the coordination reaction, the ratio of the amount of the organic ligand added to the amount of the metal salt is (0.1-10):1; and / or, The dissolving solvent is selected from any one of water, an organic solvent, and a mixed solvent of water and an organic mixed solvent; and / or, The organic solvent is selected from at least one of ethanol, methanol, isopropanol, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide and acetonitrile.
[0011] In an optional embodiment, before the coordination reaction based on the mixing of the first mixed solution and the second mixed solution, the process further includes: adding a nucleating additive to the second mixed solution; In an optional embodiment, the nucleating additive has at least one of the following characteristics: A. The nucleating additive is selected from at least one of triethylamine, ethanolamine, ammonia water, sodium acetate, glacial acetic acid and melamine; B. The amount of the nucleating additive added is 0.1% to 0.5% of the mass of the metal salt in the second mixed solution.
[0012] In an optional embodiment, the coordination reaction is carried out based on the mixing of the first mixed solution and the second mixed solution to form the metal organic framework coating layer on the surface of the lithium manganate particles to obtain a composite intermediate material, including: preheating the first mixed liquid and the second mixed liquid; After the preheating treatment, the second mixed liquid is added to the first mixed liquid, and a reaction liquid is obtained after stirring and dispersion treatment; Performing solid-liquid separation on the reaction liquid to obtain a filtrate and a filter residue; The filtrate and the filter residue are subjected to at least one set of mixing reaction treatment and solid-liquid separation treatment under stirring and dispersing treatment to obtain the composite intermediate material.
[0013] In an optional embodiment, the duration of the stirring and dispersing treatment is 2 minutes to 10 minutes; and / or, The rotation speed of the stirring and dispersing treatment is 10 rpm to 1000 rpm; and / or, The reaction temperature of the coordination reaction during the stirring and dispersing process is 30°C to 120°C.
[0014] In an optional embodiment, the coating thickness of the metal organic framework formed on the surface of the lithium manganate is controlled by repeatedly performing the mixing reaction treatment and the solid-liquid separation treatment under the stirring and dispersing treatment on the filtrate and the filter residue for a number of times; The coating thickness of the metal organic framework is 5nm~100nm; The number of treatments is 3 to 10 times.
[0015] In an optional embodiment, during the high temperature sintering process, a mixed gas of nitrogen and oxygen is introduced; and / or, During the high temperature sintering process, a mixed gas of nitrogen and oxygen is introduced, and the volume ratio of the mixed gas of nitrogen and oxygen is (1-10):100; and / or, The heating rate of the high temperature sintering process is 1°C / min to 10°C / min.
[0016] In a second aspect, the present invention provides a lithium manganese oxide composite material prepared by the preparation method of the lithium manganese oxide composite material as described in any one of the aforementioned embodiments.
[0017] In a third aspect, the present invention provides a positive electrode sheet comprising the lithium manganese oxide composite material as described in the above embodiment.
[0018] In a fourth aspect, the present invention provides a battery, comprising the positive electrode sheet described in the aforementioned embodiment.
[0019] In a fifth aspect, the present invention provides an electrical device, comprising the battery as described in the above embodiment.
[0020] Compared with the prior art, the present invention has the following beneficial effects: The present invention aims to improve the conductivity and Li ion migration kinetics of the material while maintaining electrochemical stability by constructing a metal organic framework coating layer (MOFs) on the surface of lithium manganate particles and converting it into a composite coating layer of metal oxide and carbon.
[0021] The lithium manganese oxide composite material prepared by the preparation method of the present invention achieves a significant improvement in the performance of the lithium manganese oxide material. This innovative method not only enhances the conductivity and Li ion migration kinetics of the material, but also improves the electrochemical stability and cycle life. The metal oxide / carbon composite coating layer derived from the pyrolysis of MOFs provides a fast channel for charge transfer between the electrolyte and the active components. In addition, this composite coating layer can reduce the dissolution of Mn ions, thereby extending the service life of the battery.
[0022] The preparation method of the present invention is simple, low-cost, environmentally friendly, and easy to mass-produce. Therefore, the present invention not only achieves innovation in technology, but also shows significant beneficial effects in multiple dimensions such as performance improvement, cost control, and environmental impact, providing a new direction for the development of the lithium-ion battery industry and having broad industrial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0024] Figure 1 Schematic diagram of the principle of the preparation method of the lithium manganate composite material in the embodiment of the present application; Figure 2 These are the XRD spectra of lithium manganate, ZIF-coated lithium manganate, and carbon / zinc oxide-coated lithium manganate in the examples of this application. DETAILED DESCRIPTION
[0025] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.
[0026] refer to Figure 1 In an embodiment of the present application, a method for preparing a lithium manganese oxide composite material is provided, wherein an organic ligand and a metal salt metal are reacted on the surface of lithium manganese oxide particles to form a metal organic framework coating layer, and the coating layer is converted into a lithium manganese oxide composite material composed of a composite material of metal oxide and carbon coating the lithium manganese oxide particles through a pyrolysis process.
[0027] It should be noted that metal organic frameworks (MOFs) are a class of materials with highly ordered porous structures, which are formed by self-assembly of metal ions or metal clusters and organic ligands. Due to their unique pore structure and adjustable chemical composition, MOFs have shown broad application potential in gas storage, separation, catalysis and other fields. The various technical inventions of MOFs-coated metal oxides or MOFs-derivative composite metal oxides currently developed have adopted relatively cumbersome synthesis steps, which hinders the prospects for their industrial production.
[0028] In conventional methods, MOFs are first synthesized and modified, and then ground and composited with positive electrode materials. At the same time, the technology of directly using MOFs as reactants to pyrolyze and produce carbon-loaded metal oxide materials has also been developed accordingly. However, since the oxides produced by direct pyrolysis of MOFs have problems such as small particles and low crystallinity, they are not suitable for direct use as commercial positive electrode materials. Therefore, it is crucial to develop a simple and gentle way to achieve controllable thickness of the MOFs coating layer and controllable composition of the pyrolyzed oxide and conductive carbon layer.
[0029] In the examples of this application, the application of MOFs has been extended to the field of battery materials. By constructing a MOFs coating layer on the surface of lithium manganese oxide particles and then converting it into a composite coating layer of metal oxide and carbon through a sintering process, the performance of lithium manganese oxide positive electrode materials has been significantly improved. This method not only increases the conductivity of the material and improves the migration kinetics of Li ions, but also reduces the amount of Mn dissolution and extends the cycle life of the material.
[0030] In some embodiments, the preparation method comprises: Step S1, dissolving the organic ligand in a dissolving solvent to obtain a first mixed solution.
[0031] The above steps involve dissolving the selected organic ligand (such as carboxylic acid, phenolic or amine ligand) in a suitable solvent to form a first mixed solution, wherein the dissolving solvent may be a solvent capable of dissolving the organic ligand, such as water, an organic solvent, and the like.
[0032] Through this step, a first mixed solution containing organic ligands is obtained to prepare for the subsequent coordination reaction. The dissolution of the organic ligands is conducive to the subsequent reaction with the metal salt to form a uniform metal organic framework (MOFs) coating layer.
[0033] Step S2, adding the metal salt and lithium manganate into water, and mixing to obtain a second mixed solution.
[0034] The above involves adding metal salt and lithium manganate powder into water, and uniformly dispersing them by stirring to form a second mixed solution, thereby obtaining a second mixed solution containing metal salt and lithium manganate, which provides reactants for the next coordination reaction.
[0035] The uniformly dispersed metal salt and lithium manganate are helpful to form a uniform MOFs coating layer. The water can be deionized, and the use of deionized water can reduce the interference of impurities and improve the purity of the product.
[0036] Specifically, the uniform dispersion of the metal salt and lithium manganate in water can be achieved by mechanical stirring.
[0037] It should be noted that, either step S1 or step S2 can be performed first, or they can be performed simultaneously.
[0038] Step S3, performing a coordination reaction based on the mixing of the first mixed solution and the second mixed solution to form the metal organic framework coating layer on the surface of the lithium manganate particles to obtain a composite intermediate material.
[0039] The above steps involve mixing the first mixed liquid and the second mixed liquid, forming a metal organic framework coating layer (MOFs coating layer) on the surface of the lithium manganese oxide particles through a coordination reaction, and obtaining a composite intermediate material, thereby forming a uniform MOFs coating layer on the surface of the lithium manganese oxide particles, providing a basis for the subsequent pyrolysis process.
[0040] In this step, the formation of the MOFs coating layer can be optimized by controlling the reaction conditions (such as temperature, stirring speed and time).
[0041] As mentioned above, the coordination reaction between the organic ligand and the metal salt forms the MOFs structure.
[0042] Step S4, subjecting the composite intermediate material to high temperature sintering treatment to obtain the lithium manganate composite material.
[0043] The above steps involve sintering the composite intermediate material at a high temperature to convert the MOFs coating layer into a composite coating layer of metal oxide and carbon, thereby obtaining a final lithium manganese oxide composite material whose surface is coated with a composite material of metal oxide and carbon.
[0044] The above-mentioned high temperature sintering treatment can improve the structural stability and electrochemical performance of the material.
[0045] In this embodiment, through steps S1 to S4, a composite material coating layer of metal oxide and carbon is formed on the outer surface of the lithium manganese oxide particles, which can further improve the conductivity and Li ion migration kinetics of the material, and also reduce the amount of Mn dissolution, thereby extending the cycle life of the material.
[0046] As mentioned above, the selection of organic ligands is crucial for forming a metal organic framework (MOFs) coating layer. In some embodiments, the organic ligand can be at least one of a carboxylic acid ligand, a phenolic ligand, or an amine ligand, which constructs a MOFs structure by forming a coordination bond with a metal ion.
[0047] Carboxylic acid ligands contain carboxyl groups (-COOH) and can form coordination bonds with metal ions through their oxygen atoms. Carboxylic acid ligands, for example, can include: terephthalic acid, 2-aminoterephthalic acid, 1,3,5-tri(4-carboxyphenyl)benzene, 2,5-dihydroxyterephthalic acid, etc. The advantage of carboxylic acid ligands is that they can provide multiple coordination sites, which helps to build a stable MOFs structure.
[0048] Phenolic ligands contain phenolic hydroxyl groups (-OH) and can form coordination bonds with metal ions through oxygen atoms. Examples of phenolic ligands include hydroquinone, resorcinol, 2,3,6,7,10,11-hexahydroxytriphenylene, etc. Phenolic ligands usually have strong coordination ability and can form stable coordination structures with metal ions.
[0049] Amine ligands contain amino groups (-NH2) and can form coordination bonds with metal ions through nitrogen atoms. Examples of amine ligands include: 2-methylimidazole, 2-nitroimidazole, tris(4-aminophenyl)amine, etc. The advantage of amine ligands is that they can provide nitrogen atoms with high electron density as coordination sites, which helps to enhance the stability and conductivity of MOFs.
[0050] In some embodiments, the organic ligand includes hydroquinone, resorcinol, terephthalic acid, 2-aminoterephthalic acid, 2,5-diaminoterephthalic acid, 1,3,5-tris(4-carboxyphenyl)benzene, 1,4-naphthalene dicarboxylic acid, 2,5-dihydroxyterephthalic acid, 2,2"-biphenyl dicarboxylic acid, 2,6-naphthalene dicarboxylic acid, 4,4"-stilbene dicarboxylic acid, 2,2"-bipyridine-5,5"-dicarboxylic acid, 2,2"-bipyrimidine, 2,4"-bipyridine, 2,5-dibromoterephthalic acid, 2 ,5-thiophenedicarboxylic acid, 2,6-pyridinedicarboxylic acid, 2-methylimidazole, 2-nitroimidazole, pyrazine, imidazole, 2,4,6-tri(4-pyridine)1,3,5-triazine, tri(4-iodophenyl)amine, meso-tetra(4-carboxyphenyl)porphine, 5,10,15,20-tetra(4-pyridyl)porphyrin, meta-tetraphenylporphine, 1,3,5-tri(4-pyridyl-3-phenyl)benzene, 2,5-diaminobenzenesulfonic acid, tri(4-chlorophenyl)phosphine and 1,3,5-tri(4-pyrazolyl)benzene.
[0051] In some embodiments, the metal salt is selected from at least one of an alkaline earth metal salt, a transition metal salt, or a rare earth metal salt.
[0052] In some embodiments, the chemical forms of the metal salts include nitrates, chlorides, carbonates, and acetates.
[0053] In some embodiments, the metal element in the metal salt includes at least one of Al, Mg, Ca, Sr, Ba, Fe, Ti, V, Cr, Co, Ni, Zn, Cu, Ir, W, Mo, Cd, Ag, Ce, La, Pr, Nd, Sm, Eu, Os, Nb, Zr and Y.
[0054] In some embodiments, in the reaction system of the coordination reaction, the ratio of the amount of the organic ligand added to the amount of the metal salt is (0.1-10): 1. For example, the ratio of the amount of the organic ligand added to the amount of the metal salt can be 0.1:1, 0.5:1, 0.8:1, 1:1, 3:1, 5:1, 8:1, 10:1, and the like.
[0055] In some embodiments, the dissolving solvent may be any one of the following three: (1) Water; (2) Organic solvents; (3) Mixed solvents of water and organic mixed solvents.
[0056] In some embodiments, the organic solvent is selected from at least one of ethanol, methanol, isopropanol, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide and acetonitrile.
[0057] In some embodiments, the step S3, before the coordination reaction based on the mixing of the first mixed solution and the second mixed solution, further comprises: Step S5, adding a nucleating additive to the second mixed solution; The nucleating additive is selected from at least one of triethylamine, ethanolamine, ammonia water, sodium acetate, glacial acetic acid and melamine.
[0058] In some embodiments, the nucleating additive has at least one of the following characteristics: A. The nucleating additive is selected from at least one of triethylamine, ethanolamine, ammonia water, sodium acetate, glacial acetic acid and melamine; B. The amount of the nucleating additive added is 0.1% to 0.5% of the mass of the metal salt in the second mixed solution. For example, it can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, etc.
[0059] As mentioned above, "nucleating additive" (nucleating agent) refers to an auxiliary chemical added in the process of synthesizing metal organic framework (MOFs) materials to control the crystal nucleation and growth of MOFs. The use of nucleating additives is to optimize the crystallization process of MOFs, thereby affecting the physical and chemical properties of the final material.
[0060] Nucleating agent is a substance that can promote or regulate crystal nucleation. In the synthesis of MOFs, nucleating agent can help control the nucleation rate and the number of nucleation points of the crystal, thereby affecting the growth and morphology of the crystal. The range of addition amount: the amount of nucleating agent added is 0.1% to 0.5% of the mass of the metal salt, which means that for every 100 grams of metal salt, the amount of nucleating agent used is between 0.1 grams and 0.5 grams.
[0061] In short, by adding nucleation additives to the second mixed liquid, the metal organic framework material can be nucleated in small amounts first, helping to control the crystal growth of MOFs and thus optimizing the performance of the material.
[0062] In some embodiments, the step S3, based on the mixing of the first mixed solution and the second mixed solution, performs a coordination reaction to form the metal organic framework coating layer on the surface of the lithium manganate particles to obtain a composite intermediate material, comprises: Step S31, preheating the first mixed liquid and the second mixed liquid.
[0063] In the above, the first mixed solution containing the organic ligand and the second mixed solution containing the metal salt and lithium manganate are heated to a certain temperature to promote the subsequent coordination reaction. Among them, the preheating treatment helps to improve the reaction rate and uniformity, creates conditions for forming a uniform MOFs coating layer, improves the reaction efficiency, reduces the reaction time, and thus helps to form a uniform MOFs structure.
[0064] Specifically, for example, preheating can be performed by means of a water bath, an oil bath or direct heating.
[0065] Step S32, after preheating, adding the second mixed liquid into the first mixed liquid, stirring and dispersing to obtain a reaction liquid.
[0066] As described above, after preheating, the second mixed solution is poured into the first mixed solution and stirred rapidly to ensure that the two solutions are fully mixed and dispersed. In the mixed reaction solution, the organic ligands react with the metal ions to form a MOFs structure.
[0067] Among them, rapid stirring helps to form a uniform MOFs coating layer, and uniform dispersion helps to improve the quality and performance of the material.
[0068] Specifically, a mechanical stirrer or a magnetic stirrer can be used for stirring.
[0069] Step S33, performing solid-liquid separation on the reaction liquid to obtain a filtrate and a filter residue.
[0070] After the second mixed liquid is added to the first mixed liquid and stirred and dispersed to obtain a reaction liquid, the solid in the reaction liquid (i.e., the formed MOFs-coated lithium manganese oxide) can be separated from the liquid by filtration or centrifugation, thereby obtaining a lithium manganese oxide solid containing a MOFs coating layer (filter residue) and the remaining liquid (filtrate).
[0071] Solid-liquid separation helps to purify the product, remove unreacted raw materials and by-products, and the obtained solid can be directly used for subsequent pyrolysis treatment.
[0072] Specifically, vacuum filtration, centrifugal separation or sedimentation methods may be used.
[0073] Step S34, subjecting the filtrate and the filter residue to at least one set of mixing reaction treatment and solid-liquid separation treatment under stirring and dispersing treatment to obtain the composite intermediate material.
[0074] To ensure the uniformity and integrity of the MOFs coating, the following steps can be repeated: (1) Mixing reaction treatment: Re-disperse the filter residue into the filtrate and stir and react again; (2) Solid-liquid separation: The reaction liquid is subjected to solid-liquid separation to obtain a filtrate and a filter residue.
[0075] The above-mentioned repeated process may be performed once or multiple times.
[0076] After multiple stirring, reaction and separation treatments, lithium manganese oxide particles uniformly coated with a MOFs layer are obtained, i.e., a composite intermediate material.
[0077] Multiple cycles of treatment can help improve the uniformity and quality of the MOFs coating layer.
[0078] Enhanced the electrochemical properties and structural stability of the material.
[0079] In some embodiments, the duration of the stirring and dispersing treatment is 2 minutes to 10 minutes; for example, the duration may be 2 minutes, 3 minutes, 5 minutes, 6 minutes, 7 minutes, 9 minutes, 10 minutes, and the like.
[0080] In some embodiments, the rotation speed of the stirring and dispersing process is 10 rpm to 1000 rpm. For example, the rotation speed may be 10 rpm, 20 rpm, 30 rpm, 50 rpm, 70 rpm, 90 rpm, 100 rpm, and the like.
[0081] In some embodiments, the reaction temperature of the coordination reaction during the stirring and dispersing process is 30° C. to 120° C. For example, the reaction temperature may be 30° C., 50° C., 60° C., 80° C., 100° C., 120° C., and the like.
[0082] In some embodiments, the coating thickness of the metal organic framework formed on the surface of the lithium manganate is controlled by repeatedly performing a mixing reaction treatment and a solid-liquid separation treatment on the filtrate and the filter residue under a stirring and dispersing treatment; The coating thickness of the metal organic framework is 5 nm to 100 nm; for example, the coating thickness can be 5, 10, 20, 30, 50, 80, 100, etc.
[0083] The number of treatments is 1 to 5. For example, the number of treatments may be 1, 2, 4, 5, and the like.
[0084] As described above, the filtrate and the residue are remixed and stirred and dispersed, and then the solid-liquid separation process is performed again. This process can be repeated multiple times to increase the thickness of the MOFs coating layer on the surface of the lithium manganese oxide particles. Each time this process is repeated, a layer of MOFs is added to the surface of the lithium manganese oxide particles, thereby gradually increasing the thickness of the coating layer.
[0085] In this step, the thickness of the MOFs coating is precisely controlled to optimize the material's performance. By repeating the process, a more uniform and dense coating can be achieved.
[0086] Specifically, the dispersion can be stirred by a mechanical stirrer or a magnetic stirrer, and the solid-liquid separation can be performed by filtering or centrifuging.
[0087] By adjusting the number of repeated treatments, the thickness of the MOFs coating can be precisely controlled between 5nm and 100nm. Lithium manganate particles with a specific coating thickness are obtained, which directly affects the electrochemical properties and structural stability of the material. Precise control of the coating thickness helps to improve the cycle stability and electrochemical properties of battery materials. The thickness of the coating can be adjusted as needed to meet different application requirements.
[0088] The number of repeated treatments is controlled between 1 and 5 times to achieve the desired coating thickness. By accurately controlling the number of repeated treatments, a lithium manganate composite material with a uniform coating can be obtained. Controlling the number of repeated treatments helps to achieve large-scale production and quality control. The number of treatments can be adjusted according to the characteristics of different batches of raw materials to maintain product consistency.
[0089] In some embodiments, a mixed gas of nitrogen and oxygen is introduced during the high-temperature sintering process.
[0090] In some embodiments, during the high temperature sintering process, a mixed gas of nitrogen and oxygen is introduced, and the volume ratio of the mixed gas of nitrogen and oxygen is (1-10): 100. For example, the volume ratio may be 1:100, 3:100, 5:100, 7:100, 8:100, 10:100, and the like.
[0091] In some embodiments, the heating rate of the high temperature sintering process is 1°C / min to 10°C / min. For example, the heating rate may be 1°C / min, 2°C / min, 4°C / min, 5°C / min, 6°C / min, 8°C / min, 10°C / min, etc.
[0092] The present application also provides a lithium manganese oxide composite material in an embodiment, which is prepared by the preparation method of the lithium manganese oxide composite material as described in any of the above embodiments.
[0093] The present application also provides a positive electrode sheet in an embodiment, comprising the lithium manganese oxide composite material as described in the above embodiment.
[0094] A battery is also provided in an embodiment of the present application, comprising the positive electrode sheet described in the aforementioned embodiment.
[0095] As mentioned above, the battery provided in this embodiment may be a secondary battery.
[0096] The battery may include, for example, but is not limited to, a positive electrode sheet, a negative electrode sheet, a separator, an electrolyte, etc. These components work together to ensure that the battery can store and release electrical energy safely and efficiently. Through the preparation method described in the technical disclosure book, the performance of the positive electrode material can be optimized, thereby improving the performance and reliability of the entire battery system.
[0097] An embodiment of the present application also provides an electrical device, including the battery described in the above embodiment.
[0098] As mentioned above, electrical equipment can include many types, such as portable electronic devices (smartphones, tablets, laptops, etc.), wearable devices (smart watches, health trackers, etc.), household appliances (vacuum cleaners, refrigerators, etc.), personal care equipment (electric toothbrushes, hair dryers, etc.), power tools (electric drills, electric saws, etc.), electric vehicles (including BEV, PHEV and HEV), electric bicycles and electric scooters, drones, medical equipment (pacemakers, hearing aids, etc.), industrial equipment (automated production lines, robots, etc.), communication base stations, solar energy storage systems, emergency power supplies and backup power systems (such as UPS, emergency lighting systems) and energy storage power stations, etc. These devices generally rely on batteries as energy sources, and the high-capacity, good cycle stability batteries described in the embodiments of this application can provide long-lasting and reliable power support for the above-mentioned electrical equipment to meet various power needs.
[0099] The present invention is further described below by means of specific examples, but it should be understood that these examples are only used for more detailed description and should not be construed as limiting the present invention in any form.
[0100] Table 1. Main experimental parameters in the examples
[0101] In the above table, the number of treatments refers to the number of times the filtrate and the filter residue are repeatedly subjected to the mixing reaction treatment and the solid-liquid separation treatment under the stirring and dispersing treatment.
[0102] Example 1 In this example, a lithium manganate composite material was prepared.
[0103] Experimental methods: (1) Add 1 mol of 2-methylimidazole (organic ligand) into 500 mL of water (dissolving solvent) as the first mixed solution; (2) Dissolve 1 mol of zinc nitrate (metal salt) in 500 mL of water, add 100 g of lithium manganate powder, and stir evenly to prepare the second mixed solution; (3) While stirring, the second mixed solution was quickly poured into the first mixed solution, and stirred at room temperature for 5 minutes to obtain a reaction solution; (4) The reaction solution is subjected to a vacuum filtration to obtain a filter residue and a filtrate. The filter residue is washed and dried to obtain a ZIFs-coated lithium manganese oxide material (composite intermediate material).
[0104] (5) Pyrolysis: The ZIFs-coated lithium manganese oxide material is placed in a tubular furnace and a mixture of nitrogen and oxygen is introduced, with the volume proportion of oxygen being 5%.
[0105] (6) The temperature was raised to 400°C at a rate of 5°C / min and kept at that temperature for 1 hour to obtain a zinc oxide / carbon composite material coated with lithium manganese oxide (lithium manganese oxide composite material).
[0106] The phase structure of the synthesized substance is as follows Figure 2 As shown, it shows that the materials at each stage were successfully synthesized.
[0107] Example 2 In this example, a lithium manganate composite material was prepared.
[0108] Experimental methods: The method used in this embodiment is basically the same as that in Embodiment 1, except for the specific parameters and components in Table 1.
[0109] Example 3 In this example, a lithium manganate composite material was prepared.
[0110] Experimental methods: The method used in this embodiment is basically the same as that in Embodiment 1, except for the specific parameters and components in Table 1.
[0111] Example 4 In this example, a lithium manganate composite material was prepared.
[0112] Experimental methods: The method used in this embodiment is basically the same as that in Embodiment 1, except for the specific parameters and components in Table 1.
[0113] Example 5 In this example, a lithium manganate composite material was prepared.
[0114] Experimental methods: The method used in this embodiment is basically the same as that in Embodiment 1, except for the specific parameters and components in Table 1.
[0115] Comparative Example 1 In this comparative example, the lithium manganese oxide composite material was not prepared, but the lithium manganese oxide material was directly used without any modification.
[0116] Comparative Example 2 In this comparative example, a lithium manganate composite material was prepared.
[0117] Experimental methods: The method used in this comparative example is basically the same as that in Example 1, except that the number of treatments is 20 times.
[0118] Comparative Example 3 In this comparative example, a lithium manganate composite material was prepared.
[0119] Experimental method: (1) Grind and dry-mix 100 g of lithium manganate and 10 g of aluminum nitrate. (2) Pyrolysis: Place the dry-mixed powder in a tubular furnace, and introduce a mixed gas of nitrogen and oxygen, with the volume fraction of oxygen being 10%.
[0120] (3) Heat up to 500 °C at a rate of 10 °C / min and hold for 2 h to obtain lithium manganate coated with alumina (lithium manganate composite material).
[0121] Horizontal comparison test: In this test, the following test method is adopted for testing: (1) Prepare a positive electrode sheet from the positive electrode material in the example according to the ratio of positive electrode material: conductive carbon: CNT: binder = 96:1.2:1.0:1.8.
[0122] (2) The material ratio of the negative electrode sheet is negative electrode material: conductive carbon: CMC: SBR = 95.5:0.8:1.2:2.5.
[0123] (3) Stack and assemble the positive and negative electrode sheets into a soft-pack battery cell with a capacity of 5 Ah.
[0124] (4) After formation and grading, test the high-temperature storage performance, 1C rate normal-temperature (25 °C) cycle performance, and 1C rate high-temperature (45 °C) cycle performance of the battery cell.
[0125] The test results are shown in Table 2.
[0126] Table 2. Performance test results table
[0127] In Table 2, "Ex." represents the abbreviation of the example. For example, Ex. 1 represents Example 1. Similarly, "Comp." represents the abbreviation of the comparative example. For example, Comp. 1 represents Comparative Example 1.
[0128] Analysis: (1) In Examples 1 to 5, the method provided in this application is used. Compared with Comparative Example 1, the lithium manganate material coated with the metal oxide / carbon composite material exhibits excellent cycle stability. The results of the high-temperature storage test and the high-temperature cycle test show that the coating layer of the metal oxide / carbon composite material effectively inhibits the high-temperature capacity decay caused by Mn dissolution, demonstrating the superiority of this technical invention.
[0129] (2) Comparative Example 2 has a relatively thick carbon layer, and although the conductivity is improved, it cannot inhibit the Mn dissolution of the lithium manganate material. Therefore, it exhibits poor storage performance and cycle stability.
[0130] (3) Comparative Example 3 has an alumina coating layer, which has a negative impact on the conductivity and capacity performance of the material.
[0131] According to the above experimental data and analysis, the lithium manganese oxide composite material in the embodiment shows excellent charging efficiency, shelf capacity retention rate, shelf capacity recovery rate, room temperature cycle stability and high temperature cycle stability. These results show that by constructing a metal organic framework coating layer (MOFs) on the surface of lithium manganese oxide particles and converting it into a composite coating layer of metal oxide and carbon, the electrochemical properties of lithium manganese oxide materials, including cycle stability and high temperature performance, can be significantly improved. This innovative method not only enhances the conductivity and Li ion migration kinetics of the material, but also reduces the dissolution of Mn ions and extends the cycle life of the material. Therefore, the preparation method of the present invention has achieved technical innovation and has shown significant beneficial effects in multiple dimensions such as performance improvement, cost control and environmental impact, providing a new direction for the development of the lithium ion battery industry and has broad industrial application prospects.
[0132] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a lithium manganate composite material, characterized in that: The metal organic framework coating layer is formed by reacting an organic ligand with a metal salt on the surface of the lithium manganate particle, and is converted into a lithium manganate composite material consisting of a composite material of metal oxide and carbon coating the lithium manganate particle through a pyrolysis process.
2. The method for preparing the lithium manganate composite material according to claim 1, characterized in that: include: dissolving the organic ligand in a dissolving solvent to obtain a first mixed solution; Adding the metal salt and lithium manganate into water, and mixing to obtain a second mixed solution; Based on the mixing of the first mixed solution and the second mixed solution, a coordination reaction is carried out to form the metal organic framework coating layer on the surface of the lithium manganate particles to obtain a composite intermediate material; The composite intermediate material is subjected to high-temperature sintering treatment to obtain the lithium manganate composite material.
3. The method for preparing the lithium manganate composite material according to claim 2, characterized in that: The organic ligand is selected from at least one of a carboxylic acid ligand, a phenolic ligand and an amine ligand; and / or, The organic ligands include hydroquinone, resorcinol, 2,3,6,7,10,11-hexahydroxytriphenyl, terephthalic acid, 2-aminoterephthalic acid, 2,5-diaminoterephthalic acid, 1,3,5-tris(4-carboxyphenyl)benzene, 1,4-naphthalene dicarboxylic acid, 2,5-dihydroxyterephthalic acid, 2,2'-biphenyl dicarboxylic acid, 2,6-naphthalene dicarboxylic acid, 4,4'-stilbene dicarboxylic acid, 2,2'-bipyridine-5,5'-dicarboxylic acid, 2,2'-bipyrimidine, 2,4'-bipyridine, 2,5-dibromoterephthalic acid at least one of 2,5-diaminobenzenesulfonic acid, 2,5-thiophenedicarboxylic acid, 2,6-pyridinedicarboxylic acid, 2-methylimidazole, 2-nitroimidazole, pyrazine, imidazole, 2,4,6-tri(4-pyridine)1,3,5-triazine, tri(4-iodophenyl)amine, meso-tetra(4-carboxyphenyl)porphine, 5,10,15,20-tetra(4-pyridyl)porphyrin, meta-tetraphenylporphine, 1,3,5-tri(4-pyridyl-3-phenyl)benzene, 2,5-diaminobenzenesulfonic acid, tri(4-chlorophenyl)phosphine and 1,3,5-tri(4-pyrazolyl)benzene; and / or, The metal salt is selected from at least one of an alkaline earth metal salt, a transition metal salt or a rare earth metal salt; and / or, The chemical forms of the metal salts include nitrates, chlorides, carbonates and acetates; and / or, The metal element in the metal salt includes at least one of Al, Mg, Ca, Sr, Ba, Fe, Ti, V, Cr, Co, Ni, Zn, Cu, Ir, W, Mo, Cd, Ag, Ce, La, Pr, Nd, Sm, Eu, Os, Nb, Zr and Y; and / or, In the reaction system of the coordination reaction, the ratio of the amount of the organic ligand added to the amount of the metal salt is (0.1-10):1; and / or, The dissolving solvent is selected from any one of water, an organic solvent, and a mixed solvent of water and an organic mixed solvent; and / or, The organic solvent is selected from at least one of ethanol, methanol, isopropanol, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide and acetonitrile.
4. The method for preparing the lithium manganate composite material according to claim 2, characterized in that: Before the coordination reaction based on the mixing of the first mixed solution and the second mixed solution, the method further includes: A nucleating additive is added to the second mixed solution.
5. The method for preparing the lithium manganate composite material according to claim 4, characterized in that: The nucleating additive has at least one of the following characteristics: A. The nucleating additive is selected from at least one of triethylamine, ethanolamine, ammonia water, sodium acetate, glacial acetic acid and melamine; B. The amount of the nucleating additive added is 0.1% to 0.5% of the mass of the metal salt in the second mixed solution.
6. The method for preparing the lithium manganate composite material according to claim 2, characterized in that: The method of performing a coordination reaction based on the mixing of the first mixed solution and the second mixed solution to form the metal organic framework coating layer on the surface of the lithium manganate particles to obtain a composite intermediate material comprises: preheating the first mixed liquid and the second mixed liquid; After the preheating treatment, the second mixed liquid is added to the first mixed liquid, and a reaction liquid is obtained after stirring and dispersion treatment; Performing solid-liquid separation on the reaction liquid to obtain a filtrate and a filter residue; The filtrate and the filter residue are subjected to at least one set of mixing reaction treatment and solid-liquid separation treatment under stirring and dispersing treatment to obtain the composite intermediate material.
7. The method for preparing the lithium manganate composite material according to claim 6, characterized in that: The duration of the stirring and dispersing treatment is 2 minutes to 10 minutes; and / or, The rotation speed of the stirring and dispersing treatment is 10 rpm to 1000 rpm; and / or, The reaction temperature of the coordination reaction during the stirring and dispersing process is 30°C to 120°C.
8. The method for preparing the lithium manganate composite material according to claim 6, characterized in that: Controlling the coating thickness of the metal organic framework formed on the surface of the lithium manganate by repeatedly performing a mixing reaction treatment and a solid-liquid separation treatment on the filtrate and the filter residue under a stirring and dispersing treatment; The coating thickness of the metal organic framework is 5nm~100nm; The number of treatments is 1 to 5 times.
9. The method for preparing the lithium manganate composite material according to claim 2, characterized in that: During the high temperature sintering process, a mixed gas of nitrogen and oxygen is introduced; and / or, During the high temperature sintering process, a mixed gas of nitrogen and oxygen is introduced, and the volume ratio of the mixed gas of nitrogen and oxygen is (1-10):100; and / or, The heating rate of the high temperature sintering process is 1°C / min to 10°C / min.
10. A lithium manganate composite material, characterized in that: The lithium manganate composite material is prepared by the preparation method of any one of claims 1 to 9.
11. A positive electrode sheet, characterized in that: Comprising the lithium manganate composite material as claimed in claim 10.
12. A battery, characterized in that: Including the positive electrode sheet as claimed in claim 11.
13. An electrical equipment, characterized in that: Comprising the battery of claim 12.
Citation Information
Patent Citations
Electrode material surface coating method and application thereof
CN106099047A
Lithium-rich positive electrode material based on surface modification of MOFs and preparation method thereof
CN108336316A
Positive electrode material of lithium ion battery and preparation method thereof, lithium ion battery
CN108963246A
Metal organic framework-derived phosphate composite anode material and preparation method thereof
CN109616653A
Zirconium-based MOF material-based zirconium oxide-coated lithium ion battery ternary positive electrode material and preparation method thereof
CN109950518A
Cited By
Positive electrode active material, preparation method, positive plate, battery, battery pack and electric equipment
CN120955103A